Objective measurements of skinfold thickness with a caliper show a significant relationship to total body fat percentage in dogs - Söder, Josefin; Svenningsen, Ida Eskol; Larsen, Julie Baltzer; Rasmussen, Mette Hedelund; McEvoy, Fintan J.; Stenberg, Kathrine; Bergh, Anna; Bjørnvad, Charlotte Reinhard (Frontiers in Veterinary Science, 2025)
ObjectiveNew clinical evaluation methods for estimation of total body fat percentage (BF%) in dogs are needed. The methods should be objective and reliable for accurate assessment of body composition status and to improve prevention and treatment of obesity. The aims of the study were therefore to investigate the intra- and inter-observer reliability of objective measurements of skinfold thickness with a caliper and to explore the relationship of skinfold thickness to dual-energy X-ray absorptiometry (DEXA) BF% in dogs.MethodsTwenty-three carcasses of dogs euthanatized for reasons unrelated to the study were evaluated for body condition score (BCS), bodyweight, skinfold thickness, and DEXA BF%. The results from the latter were taken as gold standard for BF% measurement. The cohort consisted of 14 different breeds, aged ≥1 year. Objective measurements of skinfold thickness were collected in triplicate by two blinded observers at the locations of the “dorsal neck,” “axillar rib,” and “lumbar back.” Statistical analyses explored intra-class correlation coefficients (ICCs) and relationships by linear models and generalized additive models (GAMs).ResultsThe dogs had a BCS of 2–9/9, a bodyweight of 2–52 kilograms, and a BF% of 6.4–74.7 percent. Objective measurements of skinfold thickness showed high intra- (range 0.991–0.993) and inter- (range 0.937–0.977) observer reliability at all locations. The skinfold thickness of the “axillar rib” in interaction with bodyweight within a spline (p = 0.0001), plus the “dorsal neck” as a linear variable (p = 0.0004), explained 73.4% of the variation in DEXA BF%. The BF% of small-sized dogs were over- and under-predicted by the prediction equation to a larger extent than for dogs of larger sizes. Due to the interaction with bodyweight, a slight variation in the low measurement values of the skinfold thickness corresponded to a large variation in DEXA BF%.ConclusionObjective measurements of skinfold thickness could be assessed with high reliability with a caliper and showed a significant non-linear relationship to DEXA BF%. Longitudinal clinical studies with larger cohorts of small-, medium-, and large-sized dogs of different breeds and BCS are warranted, to evaluate the caliper device for its potential to follow changes of BF% over time. Objective measurements of skinfold thickness may in the future be practically implemented in nutritional assessments of dogs.